Depressive symptoms and metabolic syndrome risk factors in male and female Coloradan firefighters - Voss, Corrine H., author; DeVoe, Dale, advisor; Lipsey, Tiffany, committee member; Henry, Kimberly, committee member (Colorado State University. Libraries, 2017)
Posttraumatic stress disorder (PTSD), sleeping disorders, and obesity are emerging traits among emergency workers. According to the National Fire Protection Association, as many as 37% of firefighters exhibit PTSD symptoms. Depression, distressed sleep, and PTSD are only a few symptoms associated with the rise in suicide rates among firefighters in recent years. Firefighters are also four times more likely to encounter a cardiovascular episode than the general public. Cardiovascular disease is responsible for 45% of firefighter deaths each year. Most cardiovascular disease is caused by factors that can be monitored, measured and modified. The clustering of several cardiovascular disease risk factors (abdominal obesity, hypertriglyceridemia, low HDL cholesterol, elevated blood pressure, and hyperglycemia) is termed the metabolic syndrome (MetS). MetS includes at least three of the following five characteristics: abdominal obesity (waist circumference >102 cm in men or >88 cm in women), elevated plasma triglycerides (≥150 mg/dL), decreased HDL cholesterol (<40 mg/dL in men or <50 mg/dL in women), elevated blood pressure (≥130 mmHg systolic or ≥85 mm Hg diastolic), and impaired fasting blood glucose (≥110 mg/dL). Depressive symptoms have been linked to several MetS risk factors including insulin resistance, high blood pressure and abdominal adiposity. Research suggests MetS and heart disease are caused by chronic stress and depression paired to poor health habits. Little is known, however, regarding depression and MetS among firefighters. Therefore, the purpose of this study was to examine depressive symptoms (CES-D questionnaire) and MetS risk factors among FTP firefighters through the following questions; what are depressive symptoms and MetS risk factor profiles among female firefighters compared to male? Is there an association between depressive symptoms and MetS risk factors at time one? Are depressive symptoms related to the change in MetS risk factors from time one to time two? Data was utilized from the Firefighter Testing Program (FTP), which seeks to assess known risk factors for cardiovascular disease, reduce the likelihood of developing heart and vascular disease and utilize cardiovascular risk factor status in developing individualized strategies for lifestyle changes at Colorado State University. Main findings were (1) no statistical difference between female and male CES-D depressive symptom scores, (2) no association between MetS risk factors and depressive symptoms, and (3) too small of a sample size to determine any longitudinal changes in MetS risk factors. Confounder variables within the study could be increased awareness of mental health among firefighters, low female sample sizes, acute firehouse incidents, the "healthy worker effect," increased resilience levels, or time allotted to pursuing physical fitness during shift hours. Further study with other variable relationships, larger sample sizes and following critical firehouse events should be conducted to further expand the literature. Departmental enforcement of both fitness and mental health standards would be an essential step to insure firefighter effectiveness, safety and wellbeing.